PENINGKATAN KEMAMPUAN MELAFALKAN HURUF HIJAIYAH MELALUI MEDIA KARTU HURUF PADA MATA PELAJARAN AL-QUR’AN HADITS - Laila, Uzlifatul (Journal Of Islamic Elementary School (JIES), 2017)
This research is motivated by the low ability of students to pronounce hijaiyah letters, due to the use of less effective learning media so that students are only able to memorize hijaiyah letters but do not pronounce them fluently according to the rules of makharijul letters. Students' pronunciation is also not individually corrected by paying attention to the correct letter makharijul. Of the 22 students, only 8 were successful and 14 were still incomplete. With an average score of 68.18, while the minimum completeness score criteria (KKM) is 75. To improve the ability to pronounce the hijaiyah letters, the researchers took action through letter card media which was carried out in two cycles. The formulation of the problem in this study is how to apply the Letter Card learning media to improve the ability to pronounce hijaiyah letters in the Al-Qur'an Hadith subject at MI Muhammadiyah 23 Surabaya? Then how to increase the ability to pronounce hijaiyah letters for grade 1 students of MI Muhammadiyah 23 Surabaya by using Letter Card media? This type of research is classroom action research which is carried out in two cycles. The CAR model used is the Kurt Lewin model, which in one cycle consists of four stages, which include: planning, action, observation and reflection. The data obtained were then analyzed descriptively using the formula for the average value and the percentage of learning completeness. The results showed that the application of learning to pronounce hijaiyah letters using the Letter Card media went well through improvements in each cycle. After doing the research, it is known that in the first cycle the teacher's activity score was 74 which increased to 90.5 in the second cycle. And for student activity also increased from the acquisition of a score of 69 in the first cycle to 80.43 in the second cycle. As for the completeness of reciting the hijaiyah letters, in the first cycle, the percentage of students' mastery learning outcomes was 50% which increased to 90.9% in the second cycle.